FEATURES OF THE CONCEPT STATE REGULATION OF NATIONAL DEVELOPMENT MINING INDUSTRY - YATSYKOVSKYY, Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The organization and maintenance of sustainable socio-economic progress of the country are closely connected not only with the rational use of the country's natural resources, but also with the implementation of effective state policy on the protection and reproduction of natural biogeocenoses. The construction and implementation of such a policy must meet both the tactical and long-term prospects of economic and social development of the state. The strategic importance of the mining industry for society requires regulation to ensure sustainable development and should be regulated at the state level, but to be specific to regional specifics while taking into account national interests.The article identifies the basic theoretical provisions on the need, extent and methods of regulating the economy, environmental and economic, sustainable and innovation and technological development. The task of state regulation of economic development of the mining industry is substantiated. It is proposed to consider as a set of state measures in the coal, oil and gas, metallurgy, electricity and utilities, aimed at efficient use of natural resource potential based on mining, as well as their exploration, development, primary processing, use and marketing , as a result of which there are progressive changes of production and service and structural nature in the economy of the country and its regions. The purpose of state regulation is the efficient use of natural resource potential based on the extraction of minerals from the subsoil, as well as their exploration, development, primary processing, use and marketing. A set of measures of state regulation of economic development of the mining industry in the areas of planning, regulation, regulation, supervision and control is described. Particular attention is paid to regulatory tools, namely permits with appropriate administrative support, tax, investment. In determining the specifics of regulating the development of the industry, attention is focused on its relationship with the policy documents of the national and regional levels.
Keywords: national economy; mining industry; economic development; state regulation; sustainable development